2015
DOI: 10.1108/ijrdm-04-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation, entrepreneurial orientation and business performance among small retailers

Abstract: Purpose – The purpose of this paper is to investigate the impact of market orientation (MO) and entrepreneurial orientation (EO) on business performance among small retailers. In particular, the goal is to understand and determine to what extent MO and EO influence firm performance directly, and to what extent MO and EO are connected to performance via marketing capabilities. Design/methodology/approach – The developed conceptual model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
2
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 82 publications
(179 reference statements)
6
78
2
16
Order By: Relevance
“…Competitive aggressiveness refers specifically to how a firm approaches its competitors. Multiple studies found a positive relationship between EO and small firm performance (e.g., Baker & Sinkula, 2009;Kajalo & Lindblom, 2015;Runyan, Droge, & Swinney, 2008;Wiklund & Shepherd, 2005).…”
Section: Entrepreneurial Orientation (Eo)mentioning
confidence: 99%
“…Competitive aggressiveness refers specifically to how a firm approaches its competitors. Multiple studies found a positive relationship between EO and small firm performance (e.g., Baker & Sinkula, 2009;Kajalo & Lindblom, 2015;Runyan, Droge, & Swinney, 2008;Wiklund & Shepherd, 2005).…”
Section: Entrepreneurial Orientation (Eo)mentioning
confidence: 99%
“…Lindsay and Shoham [39] Entrepreneurial orientation (Innovativeness) Market orientation, Learnning orientation Baker and Sinkula [40] Entrepreneurial orientation, Market orientation Boso et al [41] Entrepreneurial orientation, Market orientation, Network Moon [42] Entrepreneurial orientation, Market orientation, Globalization Won [43] Entrepreneurship, Social capital (Network, Trust, Norm) Yun [44] Market orientation, Network Kajalo and Lindblom [45] Entrepreneurial orientation, Market orientation, Marketing Lee and Ha [37] Entrepreneurship, Market orientation, Marketing, Networking Kwak [46] Market orientation, Technology innovation orientation Amin et al [47] Entrepreneurial orientation, Market orientation Jung and Kim [38] Entrepreneurship, Government support Buli [33] Entrepreneurial orientation, Market orientation Lee and Kim [48] Entrepreneurial orientation, Market orientation, New product development Acosta et al [34] Market orientation, Network, Entrepreneurial Orientation…”
Section: Researchers Competencesmentioning
confidence: 99%
“…The attitude of perceiving that satisfying customer needs is the key to competitiveness, and constantly trying to meet their demands with the goal of achieving customer satisfaction. 3 Choi and Lee [57] Kajalo and Lindblom [45] Network…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…The study finds the positive relationship between the CEO and the firm performance. (Kajalo & Lindblom, 2015). This is the main gap of the study and work is done using the new theories to define how Prestigious CEO affects the firm performance.…”
Section: Definitions Of Business Performancementioning
confidence: 99%